The effect of substrate rearing on growth, aerobic scope and physiology of larval white sturgeon Acipenser transmontanus. Issue 6 (24th April 2018) - Boucher, M. A.; Baker, D. W.; Brauner, C. J.; Shrimpton, J. M.
Abstract : The effect of substratum on growth and metabolic rate was assessed in larval white sturgeon Acipenser transmontanus . Yolk‐sac larvae (YSL) were reared in bare tanks or tanks with gravel as substratum from hatch until approximately 16 days post hatch (dph). The effect of an artificial substratum was also evaluated on growth alone. Substratum had a significant effect on mass, with larvae reared in gravel and artificial substrata being larger than those reared without substratum. Routine metabolic rates were significantly lower and relative aerobic scope (the difference between maximum and routine metabolic rate) was significantly higher for YSL and feeding larvae (FL) reared in gravel relative to those reared in bare tanks, particularly before fish started feeding exogenously. Furthermore, gravel‐reared larvae had higher whole‐body glycogen concentrations relative to bare‐tank‐reared larvae. Routine factorial scope (maximum metabolic rate divided by routine metabolic rate) was relatively low in all treatments (< 1·7) indicating a limited ability to elevate metabolic rate above routine early in development and mass exponents for metabolic rate exceeded 1. Taken together, these data indicate that YSL reared without substratum may divert more of their energy to non‐growth related processes impairing growth. This finding underscores the importance of adequate rearing substratum for growth of A. transmontanus and may provide support for habitat restoration and alternative hatchery rearing methods associated with sturgeon conservation.